Pengaruh Lama Waktu Biofermentasi Chromolaena odorata dengan Sumber Karbon Tepung Putak terhadap Kualitas Fisik - Tamelab, Nikanor; Oematan, Gustaf; Lestari, Gusti Ayu Yudiwati (Yayasan Sumber Daya Manusia Cerdas, 2024)
This study aims to determine the effect of the length of biofermentation time of Chromolena odorata with a carbon source of putak flour on physical quality (color, odor / aroma, texture, mold, pH and temperature). The method used is an experimental method with a complete randomized design (RAL) with 4 treatments and 4 repeats so that there are 16 experimental units. The treatment used consisted of Lb21: Biofermentation duration 21 days (as control), Lb14: Biofermentation duration 14 days, Lb7: Biofermentation duration 7 days, and Lb0: Biofermentation duration 0 days. The results of statistical analysis showed that the length of biofermentation time of Chromolaena odorata with the carbon source of putak flour had a very real effect (P<0.01) on color, aroma and temperature but a real effect (P>0.05) on texture, fungal density and pH. From the results of the study, it was concluded that the length of biofermentation time of Chromolaena odorata silage 14 days provides excellent color value and the length of biofermentation time of Chromolaena odorata 7 days which gives excellent odor / aroma and temperature value.